Association of miR-9-5p and NFIC in the progression of gastric cancer. (7th January 2022) - Lv, Shihong; Liu, Lei; Yang, Baijing; Zhao, Xiaohua
Background: Gastric cancer is the most common malignant neoplasm of digestive system. Herein, we aim to detect the expression of nuclear factor I C (NFIC) in gastric cancer cells, and to explore the effect and mechanism of its expression on the development of gastric cancer. Methods: qPCR and Western blot assays were carried out to detect NFIC expression. Then, BGC-823 and SGC-7901 cell lines were selected to perform the following functional experiments. The function of NFIC on gastric cancer cells was analyzed by biological experiments. The associations between miR-9-5p and NFIC were searched on the bioinformatics website and identified by dual luciferase assay. The effects of miR-9-5p and NFIC on cells were verified by co-transfection experiments. The related genes expression was examined by Western blot. Results: A marked augmentation of NFIC was observed in gastric cancer cells. Knockdown of NFIC significantly inhibited the viability, colony formation, invasion, and migration of gastric cancer cells. Overexpression of miR-9-5p obviously suppressed the viability, colony formation, invasion, and migration of gastric cancer cells, and this phenomenon was aggravated by si-NFIC. Additionally, the expression levels of PCNA, vimentin, and Snail were obviously decreased after miR-9-5p mimic or/and si-NFIC treatment. Conclusions: These results suggested that NFIC was highly expressed in gastric cancer cells, and knockdown of NFIC suppressed the growth and mobility of gastric cancer cells; miR-9-5p was identified as an upstream regulator of NFIC and suppressed the malignant behaviors of gastric cancer cells by targeting NFIC through affecting PCNA, vimentin, and Snail expression.